Acheulian handaxes from the Upper Siwalik in Nepal - Corvinus, Gudrun (Taylor and Francis, 2024)
A Lower Paleolithic handaxe site is recorded in folded sediments in an Upper Siwalik context in the foothills of the Himalayas in Nepal. Handaxes in the classical Acheulian tradition come from folded sandstone within the southernmost range of the Siwaliks, uplifted in the latest tectonic movement, beyond the Himalayan Frontal Thrust. Cultural remains from the Satpati Hill site consist of a number of bifacially trimmed handaxes, a pick, and some flakes and cores. These artifacts represent the oldest Lower Paleolithic evidence in Nepal, contained within uppermost Siwalik sediments. Previous finds of handaxes in Nepal have come from a post-Siwalik context at the base of alluvial deposits in the intermontane Dun valleys in the Himalayan foothills.
CRIS-Team Scopus Importer:2025-02-04